T cell subsets and their signature cytokines in infertile women prepared to undergo in vitro fertilization (IVF) - Tahsin Haias, Safin; A. Amin, Zahra (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: This study aimed to explore the immunological profile, particularly the balance between T helpers 1 (Th1), Th2, Th17, and regulatory T (Treg) cytokine responses, in women undergoing in vitro fertilization (IVF), and how these responses correlate with reproductive outcomes. It investigated the systemic levels of specific cytokines to evaluate their roles in implantation success and potential immunological barriers to fertility. Methods: A case-control study was conducted at private IVF centers in Erbil city, Iraq. Peripheral blood samples were collected and analyzed using the Human Th1/Th2/Th17/Treg Multiplex Enzyme Linked Immuno-Sorbent Assay (ELISA) Kit to quantify interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), interleukin-2 (IL-2), IL-4, IL-13, IL-17, IL-22, and IL-10 levels. Results: Significant elevations were found in Th2 cytokines (IL-4 and IL-13) and Treg cytokine (IL-10) in IVF patients compared to healthy controls (P <0.01). Th1 (IFN-γ, TNF-α, IL-2) and Th17 (IL-17, IL-22) cytokines were modestly reduced, but these differences were not statistically significant (P >0.05). Notably, anti-Müllerian hormone (AMH) levels were significantly higher in smokers, and luteinizing hormone (LH) levels were significantly elevated in women with prior IVF attempts. Conclusion: The cytokine profile suggests an immune shift toward a Th2/Treg-dominant environment in IVF patients, supporting tolerance and embryo implantation. However, excessive skewing could impair local immune readiness. The findings highlight the immunological complexity of IVF outcomes and suggest potential benefits of targeted cytokine modulation to improve reproductive success.